INFLAMMATORY BOWEL DISEASE AND ASSOCIATED SKIN MANIFESTATIONS - Usman Ghani; Mahwish Ahmed; Juwayria Omar; Amna Iqbal Butt; Athar NAyeem; Zunaira Qayyum (Journal of Ayub Medical College Abbottabad, 2024)
Background: Inflammatory bowel disease (IBD) is a group of chronic inflammatory conditions of the gastrointestinal tract. Skin manifestations are frequently found with IBD yet they are not completely comprehended regarding how common they are and whether they reflect the seriousness of disease. Objective was to determine the prevalence, type and treatment of skin recall manifestations among a cohort of patients with CD and ulcerative colitis (UC). Methods: A total of 250 IBD patients (140 CD and 110 UC) were enrolled in the study. Demographics of patients, disease duration, skin morphology were enrolled. We evaluated the frequency of skin manifestations, their association with disease activity, and course in response to therapy. Results: Skin manifestations appeared in 31.2% of patients, and were more prevalent in CD (35%) compared to UC (26%) (p=0.04). The most common skin manifestations were erythema nodosum (11.2%), pyoderma gangrenosum (5.6%), and perianal skin tags (8%). Active disease demonstrated a significant association with skin manifestations (45% active disease vs 18% remission, p<0.001). Patients receiving anti-TNF therapy had fewer new skin manifestations (20%) when compared to patients receiving conventional therapy (36%) (p=0.03), however 5% of patients receiving biologic therapy reported developing paradoxical skin reactions. Management of skin manifestations consisted mainly of systemic corticosteroid therapy, which was effective in 80% of cases, while 10% of patients with more severe perianal disease underwent surgical intervention to treat their skin manifestations. Conclusion: Skin manifestations appear to be common in patients with IBD, and a significant difference was observed between patients with CD and UC. The disease activity showed a strong association with the occurrence of skin manifestations. Anti-TNF therapy is likely to be associated with less frequent new skin manifestation, however it remains substantive that patients with biologic therapy can have paradoxical skin reactions.